Changes of hip fracture in older patients before and after the COVID-19 pandemic: a retrospective multicentre study in Japan - Shinya Tanaka; Yusuke Osawa; Yasuhiko Takegami; Nobuyuki Okui; Ken-ichi Yamauchi; Yoshiki Aoki; Shiro Imagama (BMC Musculoskeletal Disorders)
Abstract Background The COVID-19 pandemic had a significant impact on healthcare systems and the general population. However, it remains unclear to what extent these major societal changes have had an impact on the management of hip fractures in older people in Japan. Therefore, we investigated the effect of the COVID-19 pandemic on the number of patients with hip fractures, their characteristics, and their perioperative management as a retrospective multicentre study. Methods We included 1894 patients aged ≥ 65 years who underwent surgery for hip fracture at three hospitals between January 2019–December 2021. Patients were classified according to the time of injury; patients treated between January–December 2019, January–December 2020, and January–December 2021 were divided into the pre-COVID-19 group, early COVID-19 group, and late COVID-19 group, respectively. We compared age, sex, body mass index, preadmission residence, surgical procedure, length of hospital stay, waiting time for surgery, in-hospital complications, and in-hospital death. Results Our findings suggested that the early COVID-19 and late COVID-19 groups showed a 6.8% and 7.5% reduction in the number of HF patients, respectively, compared to the pre-COVID-19 group. Waiting days for surgery, length of hospital stay, and in-hospital mortality or complication rates did not significantly change before and after the pandemic. However, infection was increased in the early COVID-19 group regarding the subgroup of complications. Conclusions The COVID-19 pandemic altered the characteristics of hip fractures in older individuals.